PELATIHAN PEMBUATAN LARUTAN LIDAH BUAYA SEBAGAI ANTISEPTIK GIGI TIRUAN - Hamid, Abu; Deynilisa, Saluna; Nurhayati, Masayu; ., Listrianah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2021)
Denture cleaning methods can be done in two ways, namely mechanical and chemical. Mechanical cleaning is performed using toothbrushes, powders, pastes, or ultrasonic tools, while chemical cleaning is carried out by immersing the dentures in a cleaning solution such as in a disinfectant. The price of disinfectants and antiseptics on the market is now quite expensive, so that traditional ingredients can be used as substitutes or alternatives. One type of traditional medicinal plant that can be used is aloe vera. According to the monitoring of the service at the Elderly Dahlia Posyandu, there are those who use dentures and do not know how to make a disinfectant solution from aloe vera to treat dentures. This activity aims to train the elderly / family to make their own anti-inflammatory dentures made from aloe vera plants. The target of this training is the elderly at the Dahlia posyandu. The expected result is that the elderly can make a disinfectant solution from aloe vera to dentures.